solve for M. (m/9)+(2/3)=(7/3) Question solve for M. (m/9)+(2/3)=(7/3) in progress 0 Math Eden 5 days 2021-10-08T08:48:08+00:00 2021-10-08T08:48:08+00:00 1 Answer 0

## Answers ( )

Answer:m= 15

Step-by-step explanation:first you subtract 2/3 from both sides (m/9)+(2/3)-(2/3)= (7/3)- (2/3)

now you will have (m/9)= (5/3)

to get (m) on its own you have to multiply the both sides by 9

(m/9) times 9= (5/3) times 9

m= 45/3 or 15

Answer check:

substitute (m) for 15

(15/9)+(2/3)= (7/3)

first you should simply (15/9), so all of them will have a common denominator

(5/3)+(2/3)=(7/3)

(7/3)=(7/3)